Preliminary investigation of biodiesel reactor optimization using combine CFD-Taguchi method - Mohiuddin, A. K. M.; Adeyemi, Nabeel A. (IIUM Press, 2011)
Biodiesel is currently produced from food and non food oil sources. The process is significantly constrained by reaction kinetics and mass transfer. In the present article, preliminary investigation of the effect of reactor configuration on yield is carried out using waste cooking oil (WCO) at different reaction parameter. The Taguchi design, with temperature, impeller speed and bottom distance as process variables at 3 levels, is used to plan, analyze and optimize the process. Optimum yield was predicted for 60'C, 600 rpm and 25 mm temperature. Statistical analysis reveals the impeller distance as most significant of the variables to affect yield and a 20 computational fluid dynamics (CFO) simulation of the mixing correlated an impeller bottom clearance of 25mm to the highest yield.